Topical cetirizine and oral vitamin D: a valid treatment for hypotrichosis caused by ectodermal dysplasia. (9th August 2016) - Rossi, A.; Miraglia, E.; Fortuna, M.C.; Calvieri, S.; Giustini, S.
Abstract: Background: Ectodermal dysplasia is a clinically and genetically heterogeneous group of inherited disorders characterized by abnormal development of two or more of the following ectodermal‐derived structures: hair, teeth, nails and sweat glands. The hair is the most frequently affected structure. Hair shaft abnormalities are of great concern to these patients, but no effective treatments are available. Methods: We describe three girls with congenital hypotrichosis (9, 5 and 6 years old) caused by ectodermal dysplasia treated with topical cetirizine solution (2 mL. once daily) and oral vitamin D supplementation (1000 IU daily). Results: After 6 months of treatment, the density of hair on the scalp increased in all patients. The vellus hair was replaced by terminal hair. Hair regrowth was evaluated both from the clinical and trichoscopic point of view. Conclusion: We propose a combination of topical cetirizine and oral vitamin D as a rational treatment of choice in congenital hypotrichosis caused by ectodermal dysplasia.